2018
DOI: 10.1002/pd.5334
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal test for FGFR3‐related skeletal dysplasia based on next‐generation sequencing and plasma cell‐free DNA: Test performance analysis and feasibility exploration

Abstract: Our method had a favorable performance for noninvasively detecting fetal FGFR3 mutations in maternal plasma, highlighting its promising value in developing a noninvasive prenatal test for de novo and paternally inherited disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This further emphasises the need to involve the clinical geneticist in the prenatal evaluation of these conditions. For achondroplasia, thanatophoric dysplasia, and Apert syndrome, as well as selected other syndromes, definitive molecular diagnosis can be achieved using NIPD and analysis of cell‐free DNA in maternal blood . Of greater potential utility, but requiring invasive testing, is exome sequencing, which has the ability to screen affected pregnancies for multiple mutations in many genes, thereby increasing the possibility of arriving at a definitive diagnosis in a timely fashion in pregnancy.…”
Section: Molecular Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…This further emphasises the need to involve the clinical geneticist in the prenatal evaluation of these conditions. For achondroplasia, thanatophoric dysplasia, and Apert syndrome, as well as selected other syndromes, definitive molecular diagnosis can be achieved using NIPD and analysis of cell‐free DNA in maternal blood . Of greater potential utility, but requiring invasive testing, is exome sequencing, which has the ability to screen affected pregnancies for multiple mutations in many genes, thereby increasing the possibility of arriving at a definitive diagnosis in a timely fashion in pregnancy.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…39 Both 2D and 3D ultrasonography have limitations in the presence of a high maternal body mass index, excessive fetal movements and thoracic shadowing, particularly at later gestational ages. These limitations can to some extent be [44][45][46] Of greater potential utility, but requiring invasive testing, is exome sequencing, which has the ability to screen affected pregnancies for multiple mutations in many genes, 47 thereby increasing the possibility of arriving at a definitive diagnosis in a timely fashion in pregnancy. Exome sequencing with variant interpretation focused on a virtual panel of genes known to cause skeletal dysplasias has been shown to have a diagnostic yield as high as 83% in fetuses suspected of having a skeletal dyplasia.…”
Section: Other Imaging Aids To Sonographic Diagnosis Of Skeletal Dymentioning
confidence: 99%
“…[4][5][6] Recently, noninvasive detection of the de novo mutations causing certain autosomal dominant disease has been determined to have clinical significance. 7 Meanwhile, several studies have demonstrated the detection of fetal monogenic diseases by analyzing cfDNA using quantitative polymerase chain reaction (qPCR), digital PCR, or haplotype-assisted approaches. [8][9][10][11][12][13] The detection of monogenic diseases with such methods provides the full genotype assessment of fetus, and certain method such as the haplotype-based approaches can even interpret the inheritance of the maternal allele.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, 70% of the tests to date have been done on Chinese women. While the majority of cell‐free DNA tests are performed for the common fetal autosomal and sex chromosome aneuploidies, the test menus have expanded to include microdeletions, copy number variations, and single gene disorders . In an extraordinary study published in October 2018, Liu and colleagues performed a large‐scale population analysis using shallow sequencing data from 141 431 NIPTs performed at the Beijing Genome Institute in Shenzhen .…”
Section: Introductionmentioning
confidence: 99%